2017
DOI: 10.1016/j.virol.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome positioning in the regulatory region of SV40 chromatin correlates with the activation and repression of early and late transcription during infection

Abstract: The location of nucleosomes in SV40 virions and minichromosomes isolated during infection were determined by next generation sequencing (NGS). The patterns of reads within the regulatory region of chromatin from wild-type virions indicated that micrococcal nuclease-resistant nucleosomes were specifically positioned at nt 5223 and nt 363, while in minichromosomes isolated 48 h post-infection we observed nuclease-resistant nucleosomes at nt 5119 and nt 212. The nucleosomes at nt 5223 and nt 363 in virion chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…We have previously observed that the pattern of nucleosomes on the SV40 genome changes over the course of an infection when analyzed by MN-Seq and ChIP-Seq (2,7). In order to determine whether the pattern of nucleosome positioning when analyzed by FS-Seq also changed consistent with our previous observations, we compared results from FS-Seq to the two other techniques in SV40 chromatin isolated at 30 minutes post-infection and 48 hours postinfection.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…We have previously observed that the pattern of nucleosomes on the SV40 genome changes over the course of an infection when analyzed by MN-Seq and ChIP-Seq (2,7). In order to determine whether the pattern of nucleosome positioning when analyzed by FS-Seq also changed consistent with our previous observations, we compared results from FS-Seq to the two other techniques in SV40 chromatin isolated at 30 minutes post-infection and 48 hours postinfection.…”
Section: Resultsmentioning
confidence: 60%
“…In order to determine whether the pattern of nucleosome positioning when analyzed by FS-Seq also changed consistent with our previous observations, we compared results from FS-Seq to the two other techniques in SV40 chromatin isolated at 30 minutes post-infection and 48 hours postinfection. In our previous work with MN-Seq (7) and ChIP-Seq (2) we observed using MN-Seq that a nucleosome was present in the enhancer in chromatin from 48 hour infections which appeared to be present in much less of the chromatin in virions or at 30 minutes post infection.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations